The Relationship between Two Kinds of Generalized Convex Set-Valued Maps in Real Ordered Linear Spaces - Zhi-Ang Zhou (Abstract and Applied Analysis)
A new notion of the ic-cone convexlike set-valued map characterized by the algebraic interior and the vector closure is introduced in real ordered linear spaces. The relationship between the ic-cone convexlike set-valued map and the nearly cone subconvexlike set-valued map is established. The results in this paper generalize some known results in the literature from locally convex spaces to linear spaces.